DIVERSITY OF MOSQUITO SPECIES THAT POTENTIALLY AS A DISEASE VECTOR IN SABANG - Isfanda isfanda; Yuni Rahmayanti (Biotik, 2021)
Mosquitoes are insects that belong to Diptera order. Mosquitoes related to public health and act as vectors of disease. The mosquito genus that has been confirmed as a vector consists of Anopheles, Culex, Aedes, Mansonia, and Armigeres. This study aims to map the diversity of mosquito species in Sabang City. This study uses the Magoon trap method, which uses animals as attractants to get zoophilic mosquitoes in four different places.  Locations of data collection were carried out in Iboih Village, Balohan Village, Kenekai Village, and Paya Village. The results showed that the diversity of mosquitoes at four locations in the city of Sabang found 19 species of mosquitoes. The mosquito species found were An. leukosphyrus group, An. tesselatus, An. subpictus, An. kochi, An. vagus, An. indefinitus, Ae. albopictus, Ae. Verralina, Ae. aurentius, Ae. vexans, Cx. fuscocephalus, Cx. vishnui, Cx. quinquefasciatus, Cx. tritaeniorynchus, Cx. sitiens, Cx. gelidus, Cx. hutchinsoni, Ar. subalbatus, and Ma. dives. The entire mosquito identified are mosquitos that has been confirmed as vectors of malaria, filariasis, and arbovirosis.